If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(9x + 3) + 2(12 + -1x) = 0 Reorder the terms: 4(3 + 9x) + 2(12 + -1x) = 0 (3 * 4 + 9x * 4) + 2(12 + -1x) = 0 (12 + 36x) + 2(12 + -1x) = 0 12 + 36x + (12 * 2 + -1x * 2) = 0 12 + 36x + (24 + -2x) = 0 Reorder the terms: 12 + 24 + 36x + -2x = 0 Combine like terms: 12 + 24 = 36 36 + 36x + -2x = 0 Combine like terms: 36x + -2x = 34x 36 + 34x = 0 Solving 36 + 34x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 34x = 0 + -36 Combine like terms: 36 + -36 = 0 0 + 34x = 0 + -36 34x = 0 + -36 Combine like terms: 0 + -36 = -36 34x = -36 Divide each side by '34'. x = -1.058823529 Simplifying x = -1.058823529
| x+38=2(x+10)+4 | | 72x-44=45 | | 16=u/2 | | 0.06+2(0.07x-1)=2 | | 8x+8x+8x=143 | | -8=5n | | 7X+6x-3x-5=25 | | 10(x+2)=4(x-1) | | x^2-31x+130=0 | | 10-32=56 | | 266=-14a | | x+5y=6x+15 | | 8p=-4 | | -11+-5+-4= | | 2(x-3)-10=14 | | 72+n=78 | | -(-5/3x3) | | 30=15z | | X+18=3(2x+1) | | 7(2+3x)+12= | | 6h-3.7h= | | (9+6n)+(-5+9m)= | | N*-3+8=20 | | 5x^2-28=17 | | 3(x+4)+12=48 | | -4a-2(-6a+2)=-22 | | 7(-10-3x)=-28 | | -k^4+3k^3+9k^2+5k=0 | | -4+3y=4 | | 27=6(x-2) | | 2(d+1)=-75 | | 8(x-9)-9(x-8)=x+7-(x-1) |